ECG abnormalities and stroke incidence. (July 2013) - Agarwal, Sunil K; Soliman, Elsayed Z
In this review, the authors discuss the role of ECG in prediction of stroke. ECG plays an important role in detection of several stroke risk factors/predictors including atrial fibrillation and left ventricular hypertrophy; both are components of the Framingham Stroke Risk Score. Multiple other ECG traits have also emerged as potential predictors of stroke, namely cardiac electrical/structural remodeling – Q wave, QRS/QT duration, bundle blocks, P wave duration/amplitude/dispersion, other waveform angles and slopes; higher automaticity – ectopic beats; and re-entry – atrial tachyarrhythmia; and higher vulnerability to arrhythmia – heart rate and its variability. Most of these predictors are not ready for prime time yet; however, further research focusing on their role in risk stratification and prevention of stroke may be useful. In this article, the authors discuss the prevalence, mechanisms and clinical applications of traditional and novel ECG markers in the prevention and treatment of stroke.